Sosialisasi Pendidikan Pelestarian Laut di Desa Adat Kastala dalam Rangka Bulan Bahasa Bali V: Pengabdian Masyarakat Mandiri Sosialisasi Pelestarian Laut - Kadek Dedy Herawan; Sugiharta, I Putu Suweka Oka (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
The Balinese Language Month is a routine activity organized by the Bali Provincial Cultural Office. In 2023 the 5th Balinese Language Month takes the theme of preserving the oceans (Segara Kerthi : Campuhan Urip Sarwa Prani). As a form of support for government programs in an effort to preserve the oceans, universities also take academic steps, one of which is outreach to Traditional Villages. The efforts made by universities are not only in the theoretical dimension. The socialization of ocean conservation carried out by UHN I Gusti Bagus Sugriwa Denpasar has a real purpose. Because in academic studies it was also found that there is a gap in efforts to preserve the oceans between what is ordered by religion and the reality that is happening. Hinduism places the ocean in a very noble position both spiritually and profanely. The fact is that exploitation and pollution of the sea are increasingly happening. Through the steps in the community education method these problems are analyzed dialogically and at the same time a solution is also sought. There are many things that must be considered when carrying out community education steps so that the socialization conveyed has an impact on real behavior. The process of socializing marine conservation in Desa Adat Kastala is carried out through the stages of identifying problems, collecting materials or materials, and implementing socialization. The material presented includes teachings on ocean preservation originating from Hindu literature such as the Vedas, Puranas, Tantra, and Adi Parwa. Keywords: Socialization, Education, Marine Conservation, 5th Balinese Language Month.